2011
DOI: 10.1111/j.1365-2788.2011.01489.x
|View full text |Cite
|
Sign up to set email alerts
|

Family members' reports of the technology use of family members with intellectual and developmental disabilities

Abstract: Implications of results for technology use of people with disabilities are discussed through the lens of frequency of use and needs for individuals with disabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
1
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(83 citation statements)
references
References 20 publications
5
66
1
8
Order By: Relevance
“…Finally, despite the importance of this element, there is little documentation on the subject in the scientific literature, compared with the other dimensions presented below. This situation was previously noted by Chadwick et al (2013) and by Palmer et al (2012).…”
Section: Dimensions Associated With the Digital Inclusion Of People Wmentioning
confidence: 64%
“…Finally, despite the importance of this element, there is little documentation on the subject in the scientific literature, compared with the other dimensions presented below. This situation was previously noted by Chadwick et al (2013) and by Palmer et al (2012).…”
Section: Dimensions Associated With the Digital Inclusion Of People Wmentioning
confidence: 64%
“…The Internet can then be a "free zone," where parents and other adults have limited insight into the lives of young people. However, research has shown that family members are often the primary sources of support for new technology used among young people with intellectual disabilities (Palmer et al, 2012). Many times parents experience ambivalence when handling both technical and moral issues that come with an increased use of the Internet.…”
Section: Parents' Supportmentioning
confidence: 99%
“…Parent's support is one way to lower the barriers for young people's safe participation on the Internet. Parents promote support in the form of cognitive social strategies that could help the young person to handle every-day situations on the Internet more adeptly in combination with a supportive parent or other family members (Palmer et al, 2012). To increase young people's participation in society in general, parents think that education in combination with developed technical tools and interface is essential.…”
Section: Conclusion and Future Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Successful involvement of carers also requires that the family has access to appropriate technology and training about how they can enable the children or adults with ID whom they look after to use this technology for therapeutic purposes (Palmer, Wehmeyer, Davies, & Stock, 2012).…”
Section: Implications For Research and Practicementioning
confidence: 99%